Improving Learning Outcomes in Integrated Science on the Topic of Force through the Children’s Learning in Science Model among Grade IVb Students at Elementary School Negeri Tiakur - Knyartutu, Rogerio; Pelamonia, Johanes; Souhoka, Renny (Universitas Pattimura, 2025)
This study aims to improve student learning outcomes by implementing the Children’s Learning In Science (CLIS) learning model in Class IVb of SD Negeri Tiakur, Moa District, Southwest Maluku Regency. The study used a classroom action research (CAR) method, conducted at the school with 32 students as research participants. Data were collected through observation, documentation, and written tests. The results showed a significant improvement in student learning outcomes. In the initial test, only 12 students (37.5%) achieved the Minimum Mastery Criteria (MMC). After applying the CLIS model in Cycle I, the number of students who met the MMC increased to 19 (59.5%). In Cycle II, all students (100%) successfully achieved scores that met the MMC. This improvement indicates that constructivist-based learning such as CLIS helps students develop a deeper understanding of scientific concepts. Therefore, the CLIS model is highly recommended for use in science learning at the elementary school level. This model also effectively increases students' active participation during the learning process.